EFEKTIVITAS KAMPANYE GO GREEN DALAM LAYANAN GOGREENER GO FOOD TERHADAP PERILAKU PEDULI LINGKUNGAN (Survei Pada Followers Instagram @gojekindonesia) - Anisa Ramadhani (2020)
This research aims to know about how much the effectiveness of the go green campaign in the gogreener go food service on enviromental care behavior (survey on Instagram followers of @gojekindonesia.) The relevant model in this research is the AIDDA. The research was conducted using a quantitative research approach. The research method used is the survey method. The population is Instagram followers of @gojekindonesia with a sample of 100 respondents. The sampling technique uses non probability technique with purposive sampling. Analysis technique to measure the effect of variable X and Y uses a regression test. Data testing techniques were processed using SPSS (Statistical Product and Service Solution) version 26. The results of this research indicate that the correlation of X variable with Y variable is strong and the regression test has a positive effect. These results are supported by the result of the hypothesis test significance of tcount > ttable, namely 9,5415 > 1,98447 which Ho is rejected and Ha is accepted means that the effectiveness of the go green campaign in the gogreener go food service has a big effect on the enviromental care behavior of @gojekindonesia's followers. Keywords: Go Green Campaign, Enviromental Care Behavior, Gogreener Service, Gojek